Profilin protein as a clinically significant panallergen in the development of pollen-food allergy syndrome - O.P. Volosovets; S.P. Kryvopustov; O.V. Mozyrskaya; M.V. Kryvopustova (Zaslavsky O.Yu., 2019)
Profilin plays an important role as a sensitizer and factor that presents difficulties both in the diagnosis and in the treatment of patients with pollen-food allergy syndrome. According to some publications, its value in people allergic to latex remains low or even absent. In controlled studies, profilin proved its ability to cause various symptoms of upper and lower respiratory tract diseases. The clinical significance of profilin in the development of respiratory disease in real world and the extent to which it contributes to the onset of symptoms have not been fully investigated. The role of profilin in the development of an oral allergic syndrome to plant products has been recognized in patients with pollen allergy. In addition, profilin can cause systemic reactions to plant foods in certain geographical areas with high levels of grass pollen. Despite the aforementioned relevance, there is no reliable therapeutic approach to the treatment of profilin protein allergy. In addition to it, allergen-specific immunotherapy is not recommended for patients with profilin sensitization, due to the absence of minor components in the preparations for this type of therapy, and the effectiveness of food immunotherapy has not been proven. Thus, preventive strategies, namely elimination and symptomatic therapy, may be the best treatment options for patients sensitized to profilin.